2005
DOI: 10.1007/s10669-005-4273-y
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Evaluation of Biological Effects on Human Keratinocytes Exposed to 900 MHz Electromagnetic Field

Abstract: The biological effects of electromagnetic radiation at ultra high frequency on human keratinocytes were investigated. HaCaT cell system, a spontaneously immortalized human keratinocytes cell line, was chosen as model since skin is usually exposed to electromagnetic radiation at considered frequency more than inner tissues. HaCaT cells were exposed to a pure sinusoidal field at a frequency of 900 MHz (average SAR levels ranging from 0.04 to 0.08 W/kg) in plane wave condition inside a GTEM chamber for time inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 21 publications
2
5
0
Order By: Relevance
“…Similar negative results have been obtained on rat skin with up to 5 W/kg SAR values [Sanchez et al, 2008]. However, lower SAR EMF emitted by a transverse electromagnetic cell (4-8 mW/kg for 18 h, 900 MHz) significantly reduced the growth of exposed human skin cells and caused an increase in the expression of keratin 1 and involucrin [Duranti et al, 2005]. In addition, a 1 h exposure to GSM radiation (1.3 W/kg, 900 MHz, halfwave dipole) generated altered protein expression in human skin in vivo [Karinen et al, 2008].…”
Section: High-throughput Screening Approaches and Resultssupporting
confidence: 77%
See 1 more Smart Citation
“…Similar negative results have been obtained on rat skin with up to 5 W/kg SAR values [Sanchez et al, 2008]. However, lower SAR EMF emitted by a transverse electromagnetic cell (4-8 mW/kg for 18 h, 900 MHz) significantly reduced the growth of exposed human skin cells and caused an increase in the expression of keratin 1 and involucrin [Duranti et al, 2005]. In addition, a 1 h exposure to GSM radiation (1.3 W/kg, 900 MHz, halfwave dipole) generated altered protein expression in human skin in vivo [Karinen et al, 2008].…”
Section: High-throughput Screening Approaches and Resultssupporting
confidence: 77%
“…This observation can be correlated to lower power efficiency and coupling of EMF to the biological samples in comparison to plane-wave emitting devices. However, other work has shown that such low SAR (40-80 mW/kg, 900 MHz) could significantly influence the physiology of human cells [Duranti et al, 2005].…”
Section: Reverberation Chamber For Bio-electromagnetic Experimentationmentioning
confidence: 96%
“…We could quote for example the anechoic chamber, and also Transverse ElectroMagnetic (TEM) cells [3,4]. TEM cells have been recently used as in vivo exposure tools in bioelectromagnetic experiments such as cerebral changes in rats [5].…”
Section: Exposure Setups For Bioelectromagnetic Experiments In High Fmentioning
confidence: 99%
“…Thus, the relation (4) was used for two distinct setups using respectively nine locations (calibration for empty MSRC) and four points (in the presence of the biological incubator). Consequently, it also appeared more convenient to refer indifferently to ↔ E max tot using quantity in (4) defined for N = 9 or N = 4.…”
Section: Definition Of Electromagnetic Validating Criteriamentioning
confidence: 99%
See 1 more Smart Citation